Improving palliative care outcomes in remote and rural areas of LMICs through family caregivers: lessons from Kazakhstan - Salikhanov, Islam; Katapodi, Maria C.; Kunirova, Gulnara; Crape, Byron L. (Frontiers in Public Health, 2023)
60 million people require palliative care worldwide, and nearly 80% of them live in LMICs. Providing palliative care in remote and rural areas of LMICs requires special consideration to ensure equitable access. This perspective aims to deliver context-oriented policy recommendations to improve palliative care outcomes in Kazakhstan by capitalizing on existing resources considering its geopolitical and sociocultural context. With half of the population in Kazakhstan residing in rural regions, the provision of healthcare services, specifically palliative care, mandates particular attention to ensure equal access to high-quality care. To understand the challenges of implementing palliative care in remote regions of Kazakhstan and to propose tailored solutions, 29 key stakeholders: family caregivers, health professionals, and palliative care administrators, were identified in five regions of Kazakhstan. The main challenges encountered by family caregivers include a lack of palliative care skills, the need for home care from mobile services, and high out-of-pocket expenditures. The challenges highlighted by healthcare providers and administrators were the lack of formal education in palliative care, the shortage of opioids, and limited societal awareness and state support. Based on challenges elaborated by stakeholders and literature, this perspective advocates against replicating the strategies implemented in high-income countries. Family caregivers play a critical role in implementing affordable and efficient palliative care in resource-limited settings. Enhancing their competencies through training and increasing access to palliative care services through mobile teams are tailored and localized solutions that address specific challenges in Kazakhstan which can potentially benefit 48 million individuals who require these services worldwide.